Kontribusi Sosial Agama Modin dalam Menghadapi Transformasi Budaya Nyadran di Pagelaran Malang - Sholichah, Norma Ita (LP3M IAI Al-Qolam, 2018)
This study aims to find out the modin social contribution to the transformation of nyadran tradition in Pagelaran Malang, as well as the concrete forms of modin's involvement in the transformation of the tradition. This study uses descriptive qualitative research method that seeks to produce descriptive data in the form of narration about the observed phenomena, expressions or notes that occur during the research process naturally and holistically (intact). This research was conducted in Pagelaran, a sub-district of Malang Regency, namely in the Village of Banjarejo and the Hamlet of Sukoarum. In connection with the main issues, namely the role or social contribution of modin in the nyadran cultural transformation, there were several findings: (1) the social contribution of modin is coordinating with religious leaders and elders to holding tahl?l and istigh?tsah at the nyadran in Sukoarum, compiling the Islamic nyadran program in collaboration with other village officials for it, socializing nyadran to the hamlet communities order to participate in preserving the culture, as well as participating and at the same time as the coach of the tradition in the hamlet, (2) the concrete forms of Modin's involvement in the nyadran transformation are: actively participating in tahl?l and istigh?tsah in pasarean (cemetery) Sukoarum until now, monitoring Islamic religious activities at the location of the pasarean by holding tahl?l every thursday night legi, working with donors to participate in orphanage compensation every nyadran on 1 Muharram (1 Suro), in collaboration with the Hamlet Head of Sukoarum to continue preserving the cultural tradition of nyadran.